EVALUATION OF THE IMPLEMENTATION OF THE CHILD-FRIENDLY SCHOOL PROGRAM AT SDN DEWI SARTIKA CIPTA BINA MANDIRI, SUKABUMI CITY - GARWAUTAMI, Paramadita Khalifa (Journal of Education and Leadership in Education, 2024)
This study evaluates the implementation of the Child-Friendly School (SRA) program at SDN Dewi Sartika CBM, Sukabumi City, using the CIPP (Context, Input, Process, Product) model. The research uses a mixed-method approach, involving principals, teachers, facilitators, students, parents, school committees, and alumni parents as subjects. Data were collected through observation, interviews, questionnaires, and documentation. The findings show that the SRA program at SDN Dewi Sartika CBM effectively meets students' character education needs. At the context stage, the program's goal is to ensure students have the right to learn in a safe, comfortable environment, with qualified educators who understand children's rights and use child-friendly teaching methods. In the input aspect, the resources supporting the SRA program are evaluated to see if they align with the plan. The evaluation reveals that the school's vision, mission, and goals include the SRA program. The process evaluation shows that the SRA program has been integrated into the learning activities. Finally, the product evaluation indicates that the program has achieved its goals, based on interviews, documentation, and questionnaires. Recommendations include increasing awareness and socialization about the SRA program to ensure all school residents understand its importance. Educators and staff should participate in in-service training related to the program. Collaboration between the school and parents is needed to improve communication about students' behavior and character development both at home and school. Consistency in attitudes toward the SRA program among educators and staff is necessary to set a good example for students.